Fatty Acids of CLA-Enriched Egg Yolks Can Induce Transcriptional Activation of Peroxisome Proliferator-Activated Receptors in MCF-7 Breast Cancer Cells. (26th March 2017) - Koronowicz, Aneta A.; Banks, Paula; Master, Adam; Domagała, Dominik; Piasna-Słupecka, Ewelina; Drozdowska, Mariola; Sikora, Elżbieta; Laidler, Piotr
Abstract : In our previous study, we showed that fatty acids from CLA-enriched egg yolks (EFA-CLA) reduced the proliferation of breast cancer cells; however, the molecular mechanisms of their action remain unknown. In the current study, we used MCF-7 breast cancer cell line to determine the effect of EFA-CLA, as potential ligands for peroxisome proliferator-activated receptors (PPARs), on identified in silico PPAR-responsive genes: BCAR3, TCF20, WT1, ZNF621, and THRB (transcript TR β 2). Our results showed that EFA-CLA act as PPAR ligands with agonistic activity for all PPAR isoforms, with the highest specificity towards PPAR γ . In conclusion, we propose that EFA-CLA-mediated regulation of PPAR-responsive genes is most likely facilitated by cis9, trans11CLA isomer incorporated in egg yolk. Notably, EFA-CLA activated PPAR more efficiently than nonenriched FA as well as synthetic CLA isomers. We also propose that this regulation, at least in part, can be responsible for the observed reduction in the proliferation of MCF-7 cells treated with EFA-CLA.